THE USERS OF LITHUANIAN ACADEMIC LIBRARIES ELECTRONIC CATALOGUE - PEČELIŪNAITĖ, ANGELĖ (Knygotyra, 2014)
The Internet and information and communication technology, giving the user the unlimited potential to achieve, process, share and disseminate information, to communicate in various forms inevitably affect human behaviour, changing our habits. Information managing institutions have identified this challenge and seek the possible ways how to best meet the needs of users. They are constantly interested in the behavioural changes of information consumer and monitor the flow and timely response to the changing developments. This article presents the research of electronic cataloque sites of the Lithuanian Academic Library using Google Analytics website analysis tool, which allows to capture a time variation in consumer behaviour. A one-year long fact-finding and data analysis revealed a growing desire of information users to work with mobile devices. The following trends have also been identified – the average time on visiting the site is shorter, the bounce rate has increased, the number of pages viewed during the session has decreased.
Keywords: ...